The Profile of Upper Gastrointestinal Endoscopy in Deli Serdang Hospital - Herryanto Lumbantobing; Leonardo Basa Dairi; Juwita Sembiring; Mabel Sihombing; Betthin Marpaung; Sri Maryuni Sutadi; Lukman Hakim Zain (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Background: Upper gastrointestinal endoscopy profile has been reported by many hospitals; however, there has never been from Deli Serdang hospital, North Sumatera. The aim of study was to determine the profile of upper endoscopy at Deli Serdang hospital. Method: The study was conducting retrospectively 453 patients during the period of December 2006– December 2008 at the Endoscopy Unit Department of Internal Medicine Deli Serdang hospital. Data were obtained from medical records including the age, sex, race, indications, and endoscopic diagnosis. All data were reported descriptively. Results: Out of 453 patients who underwent upper gastrointestinal endoscopy, 241 (53.20%) patients were male. The mean age was 66.3 ± 15.6. Most patients (51.88%) were between 40-59 years of age. Regarding the ethnicity, there were 30.91% Bataknese patients, 21.85% Javanese, 18.98% Karonese, 14.79% Malays, and 13.47% patients of other ethnicities. Dyspepsia was the mostly found indication, which was found in 75.94% patients. It was followed by hematemesis/melena in 15.01% patients and other indications in 6.84% patients. About 33.11% patients had normal upper gastrointestinal diagnosis; while gastritis was found in 26.93% patients, erosive gastritis in 18.98% patients, gastric/duodenal ulcer in 8.83%, and esophageal varices in 5.74% patients. Conclusion: About 453 patients have undergone upper gastrointestinal endoscopy during 2 years period. This study shown greater number of male patients compared to female and the patients were most frequently between 40-59 years old. Normal upper gastrointestinal diagnosis was the most frequently found in this study. Keywords: upper gastrointestinal endoscopy, profile, indications, endoscopic diagnosis